Legionella effector Lpg1137 shuts down ER-mitochondria communication through cleavage of syntaxin 17 - Kohei Arasaki (Nature Portfolio, 2017)
The pathogenic bacteriumLegionella pneumophila replicates within macrophages. Here, the authors show that L. pneumophilasecretes an effector protein that cleaves the host protein syntaxin 17, thus inhibiting autophagy and staurosporine-induced apoptosis in the host cell.